2018
DOI: 10.3892/ijo.2018.4379
|View full text |Cite
|
Sign up to set email alerts
|

Methyl ferulic acid exerts anti-apoptotic effects on L-02 cells via the ROS-mediated signaling pathway

Abstract: The present study aimed to investigate the anti-apoptotic effects of methyl ferulic acid (MFA) on L-02 cell apoptosis induced by ethanol, and to elucidate the possible underlying mechanisms. L-02 cells were examined after being soaked in ethanol (400 mM) to allow the ethanol to permeate into the cells for 24 h. Cell survival was measured by MTT assay. Cell apoptosis was assessed by both flow cytometry and single-stranded DNA assays. Intracellular reactive oxygen species (ROS) production was determined using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…In line with our findings, a previous study found that low doses of FA has antiapoptotic effect mediated via upregulating of sirtuins proteins in PC12 cells (Moghadam et al, 2018). Similarly, it has been reported that FA derivative attenuated ethanol-induced apoptosis in cell line by inhibiting ROS and MAPK signaling pathways (Li et al, 2018).…”
Section: F I G U R Esupporting
confidence: 92%
See 1 more Smart Citation
“…In line with our findings, a previous study found that low doses of FA has antiapoptotic effect mediated via upregulating of sirtuins proteins in PC12 cells (Moghadam et al, 2018). Similarly, it has been reported that FA derivative attenuated ethanol-induced apoptosis in cell line by inhibiting ROS and MAPK signaling pathways (Li et al, 2018).…”
Section: F I G U R Esupporting
confidence: 92%
“…In line with our findings, a previous study found that low doses of FA has antiapoptotic effect mediated via upregulating of sirtuins proteins in PC12 cells (Moghadam et al., 2018). Similarly, it has been reported that FA derivative attenuated ethanol‐induced apoptosis in cell line by inhibiting ROS and MAPK signaling pathways (Li et al., 2018). Furthermore, FA was reported to protect cortical neurons against glutamate‐induced apoptosis by upregulating Bcl‐2, antiapoptotic marker, mediated by activation of PI3K/Akt as well as enhancement of MEK/ERK signaling pathway that hinder caspase activation and preventing mitochondrial release of cytochrome c (Jin et al., 2007).…”
Section: Discussionmentioning
confidence: 75%
“…Numerous studies have shown that alcohol can cause alcoholic liver damage by activating oxidative stress, inhibiting liver fat-acid metabolism, and increasing liver lipid synthesis (Li et al, 2017;Li et al, 2018;Yang C. F. et al, 2018). Studies have also revealed that alcohol reduces hepatic glycogen synthesis and increases gluconeogenesis by regulating the liver insulin signaling pathway (Pang et al, 2009;Magdaleno et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, Chinese herbal medicine for the prevention and treatment of insulin resistance has become a research hotspot domestically and overseas. Methyl ferulic acid (MFA) is a white needle compound that possesses a variety of pharmacological properties, including antioxidant stress, anti-apoptosis, and anti-inflammatory effects (Li et al, 2017; Cheng et al, 2018; Li et al, 2018; Yang et al, 2018; Cheng et al, 2019). However, to our knowledge, there are still no reports concerning the effect of MFA on insulin resistance at home and abroad.…”
Section: Introductionmentioning
confidence: 99%